SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN KREDIT MENGGUNAKAN METODE DECISION TREE (STUDI KASUS : BANK PD. BPR GEMILANG TEMBILAHAN) - M. Fahrizal Akbar; Samsudin Samsudin (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2016)
Bank PD BPR Tembilahan is a banking company which give credit to customers. There are so many rivals in giving credit, That’s way it needs detail in giving credit to customers avoiding disadvantages to the company. Covering those problems they create a system. A system that sureness in giving credit to customers, it makes a few mistake in giving credit and time. This system is build by using decision tree method to deciding fit for credit. Implementation system using PHP and MySQL database. This system is one of alternative solution in judging fit for credit process.Keywords: Decision tree, Credit, MySQL, PHP, System.